Motherless Youth: Exploring Social, Emotional, and Economic Effects of Motherlessness on Youth in Madombidzha Village. - Ramatswi Talifhani Trevor; Nwanamidwa Pfarelo (CV. RADJA PUBLIKA, 2025)
This study investigates the profound effects of motherless youth in Madombidzha Village, aiming to understand the social, emotional, and economic implications of this phenomenon. The problem of motherlessness is increasingly prevalent, leading to various challenges for young individuals, including increased vulnerability to mental health issues, lower educational attainment, and higher rates of delinquency. This study seeks to highlight these issues and their broader impact on the community. A qualitative research approach was employed, which is crucial for gaining in-depth insights into the lived experiences of youth affected by motherlessness. Data was collected through semi-structured interviews with affected youths, community leaders, and social workers, providing a comprehensive understanding of the issue from multiple perspectives. The findings reveal that motherlessness contributes to a significant decline in self-esteem among youth, fosters a sense of abandonment, and correlates with increased risk-taking behaviors. Additionally, the study underscores the importance of community support systems in mitigating these effects. The significance of this study lies in its potential to inform local policy, enhance community programs, raise awareness about the challenges faced by motherless youth, and contribute to the broader discourse on family dynamics and youth development. Keywords: Motherlessness, youth, Madombidzha Village, mental health, community support, qualitative research.